Strategy to Improve English Vocabulary Achievement during Covid-19 Epidemic. Does Quizizz Help? - Huei, Law Szee; Yunus, Melor Md; Hashim, Harwati (Journal of Education and e-Learning Research, 2021)
Science, Technology, Engineering, and Mathematics (STEM) education is being increasingly recognized as needing vital emphasis at a national level. To enhance learning in Science and Mathematics, the repertoire of vocabularies plays a significant role. As the coronavirus disease 2019 (COVID-19) continues its spread across the world, people’s vocabulary learning has been limited. Responding to this situation with appropriate awareness, e-learning is being applied to teach the English language. The intent of this study is to utilize Quizizz to enhance the vocabulary achievement among primary English as Second Language (ESL) pupils in rural schools. The study’s research employed mixed methods with purposive sampling of 13 participants. The research site was a rural school located 60km from the nearest town. The data were collected both pre and post-test as designed by the researcher and Likert scale questionnaire. The data was analyzed using appropriate quantitative analysis. To shed more light on the implementation, a thematic analysis by use of a semi-structured interview was conducted. The study finds that 10 out of 13 participants have shown an increase in their post-test of filling in the blank scoring test. The data is strengthened by a moderately high mean score of a Likert scale questionnaire. Furthermore, the participants highlighted that the Quizizz’s leaderboard matched their favored learning style. In this way, this feature tends to evoke a positive learning atmosphere. Thus, it can be concluded that Quizizz could enhance vocabulary achievement among primary English as Secondary Language (ESL) pupils in rural schools.